Ímpetu y sueño del arte norteamericano en los escritos de Aguilera Cerni - Bernárdez Sanchís, Carmen (Revista Complutense de Historia de América, 2010)
The present text focuses on two books about art from the United States written by critic and historian Vicente Aguilera Cerni in 1955 and 1957, respectively. Through them, and the historical circumstances surrounding them, we analyze how U.S .art was interpreted during the Franco regime, and the role it played in Spanish art circles after its “discovery.” Aguilera Cerni’s books were written in a period of Spanish history running between accord and embrace, a phrase associated with political relations between Spain and the United States in the 1950s. In that context, “accord” refers to economic and political accords signed by the governments of Spain and the United States in 1953. The subsequent “embrace” took place between Franco and President Eisenhower in 1959. While Aguilera Cerni’s theoretical legacy is now recognized, it has yet to be sufficiently studied. The present text analyzes one of his leastknown and most innovative contributions to art history: his open and progressive presentation to the Spanish public of U.S. artistic creations practically unknown in Spain at that time. Those works had never been studied here and very few of the studies by foreign authors had yet been translated.
Keywords: Art History; Aguilera Cerni; United States of America; Identity; Painting; 20th Century